Bridging Tradition with Science in Persian Manuscript Restoration: A Comprehensive Review of Eremurus (Seriš) Adhesive - Barkeshli, Mandana (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2025)
The illustrious history of bookmaking in Iran is a testament to the synergy of art and craftsmanship. It reflects an era when a collective of artisans, from papermakers to bookbinders, converged within the royal kārkhāne (workshops) to create literary masterpieces. These skilled individuals not only crafted new codices but also played a pivotal role in restoring manuscripts affected by time and the elements, thereby blending art with preservation. Persian bookbinders, traditionally known as ṣaḥḥāfi or jeld-sāzi, were custodians of both the aesthetic and structural integrity of books, undertaking tasks ranging from binding to conservation. Their expertise extended to an array of related crafts, underscoring their central role in the cultural stewardship of written heritage. In the crucible of these time-honored practices, Eremurus (Seriš) emerged as a vital material, valued for its adhesive qualities essential for manuscript conservation. This paper review aims to elucidate the intersection of traditional restoration practices and modern scientific research on Seriš. By synthesizing recent advances with historical insights, the review underscores Seriš’s enduring significance and potential to enhance contemporary conservation methods, drawing from a rich legacy of Persian craftsmanship to inform and elevate modern practices. In examining the evolution of terminology and practice—from the warrāq and mojalladgar of the past to the maremat-gar of today—the review contemplates the transformation of conservation roles. It explores how the wisdom of yesteryears, encapsulated in the use of Seriš, can be harmonized with innovative scientific approaches to secure the legacy of Persian manuscripts for future generations.